Factors Influencing on Chronic Bacterial Osteomyelitis Recurrence in Shaft of Lower Limb Bones After Surgery - Al-Ahmer, Haitham; Al-Daoud, Fouad; Mushtaq, Gohar; Emara, Khaled (Journal of medical and pharmaceutical sciences, 2024)
Objectives: Effecting of risk factors, particularly uncontrolled diabetes, smoking, fracture classification at initial injury and preoperative laboratory results on osteomyelitis recurrence rate. Additionally, it aimed to evaluate the outcomes of qualitative surgery in the presence of these factors. Materials and Methods: (Prospective study) 31 patients diagnosed chronic bacterial osteomyelitis with a mean age of 36.7 years and an average follow-up duration of 18 months (9-30). These patients were admitted between January 2021 and July 2023. Clinical, radiological, and laboratory findings, treatment methods, surgical outcomes, and recurrence rates were recorded. Data on patients' medical histories, habits, and disease characteristics were collected, including a detailed history of the initial bone injury, its treatment, and clinical features. The primary treatment outcome measures were bone result and osteomyelitis recurrence. Results: Osteomyelitis was observed in only 5 out of 31 patients (16.1%). In the statistical analysis, according to Pearson's correlation analysis, diabetic patients were more susceptible to osteomyelitis recurrence (p=0.000224), indicating a significant association between osteomyelitis recurrence and uncontrolled diabetes. However, the correlation analysis for fracture classification and smoking (p=0.260 and p=0.293, respectively) showed no association with the rate of recurrence. Similarly, preoperative laboratory results (CRP, CBC, ESR) (P=0.524, P=0.496, P=0.082) indicated no correlation between recurrence rate with smoking, fracture classification, and laboratory results.
Keywords: Osteomyelitis; recurrence; Smoking; Fracture classification; Diabetes; Laboratory